A model-based vision system for recognising three-dimensional objects from a single gray-intensity image - Li, Yiwu. (2008)
This project considers the problems of feature extraction, pose estimation and identification of spatial objects under different working environments, lighting conditions and camera projections. A model-based recognition system is proposed and implemented for identifying and estimating the pose of target objects comprising of straight and well-defined curve segments form a single image.